Implementation of Ecotourism Program as an Effort to Develop Village Tourism Potential in Serdang Wetan, Tangerang: Community Service Activities - Dabella Yunia; Titis Nistia Sari; Deris Desmawan; Rizal Syaifudin; Sugeng Setyadi (MOVE: Journal of Community Service and Engagement, 2023)
This article discusses the implementation of ecotourism program as an effort to develop village tourism potential in Serdang Wetan, Tangerang, through community service activities. The purpose of this article is to describe the process of community service activities carried out to enhance the skills and understanding of the village community and tourism developers in developing sustainable ecotourism that has positive impact on the surrounding environment. The methods used are through training, mentoring, and tourism promotion. The results of this community service activity are increasing awareness of the village community in tourism management, increasing the number of visitors and revenue from tourism, and helping to preserve the culture and environment in the area. In conclusion, community service activities in Serdang Wetan Village Tangerang have the potential to become a model for tourism development in other areas, especially in rural areas that have untapped tourism potential